Third National Summit on Promoting Well-Being and Resilience in Healthcare Professionals: Abstracts from the Poster Winners - Building Healthy Academic Communities BHAC Journal (The Ohio State University Libraries, 2022)
Symptoms of burnout, depression, and anxiety are experienced by more than half of all healthcare providers across the country. Like the general population, healthcare providers also engage in unhealthy lifestyle behaviors which can contribute to suboptimal mental health and chronic disease outcomes. Further, the mental and physical well-being of providers has been linked to the quality, safety, and cost of patient care. To address these critical issues, The Ohio State University partnered with the National Academy of Medicine's Action Collaborative on Clinical Well-being and Resilience to bring together hundreds of clinicians, leaders, influencers, students, and agents of change for the Third National Summit on Promoting Well-Being and Resilience in Healthcare Professionals. The summit took place September 28-30, 2022, in Columbus, Ohio. In addition to including phenomenal presentations from some of the nation's brightest minds, expert practitioners, and renowned motivational speakers, the Summit also included judged poster sessions. BHAC is pleased to present the following abstracts from the winning posters.   More information about the National Summit on Promoting Well-Being and Resilience in Healthcare Professionals is available at: https://clinicianwellbeing.osu.edu/